Exogenous riboflavin-induced modulation in physio-biochemical attributes in drought-stressed canola (Brassica napus L.) plants - Ijaz, Muneeza; Sajjad, Muhammad; Akram, Nudrat Aisha (International Journal of Applied and Experimental Biology, 2026)
Drought stress adversely affects plants throughout their life cycle, from seed germination to full maturity, by impairing metabolic and physio-biochemical processes, ultimately reducing yield. Riboflavin, a water-soluble vitamin, is pivotal in photosynthesis and has been reported to promote growth and stress resistance in plants. To evaluate the efficacy of riboflavin in mitigating drought-induced adversaries, a trial was carried out on two Brassica napus L. (canola) cultivars, Super and TM, in two different water levels: 100% (well-watered) and 60% (drought-stressed) soil field capacity. Each treatment was replicated three times. Seeds were pre-soaked in a 100 µM riboflavin solution for 14 hours before sowing, and foliar application was applied after a 30-day drought period. Water deficit stress was imposed 15 days after germination and maintained for 30 days, and plants were collected after 15 days to determine morphological and physio-biochemical parameters. Drought stress significantly suppressed leaf area, and shoot and root biomass of both canola cultivars; it also markedly decreased the levels of chlorophyll (a, b, and total). In contrast, under drought conditions, there was a rise in relative membrane permeability, chlorophyll a/b ratio, levels of H₂O₂, MDA, glycine betaine, total soluble proteins, ascorbic acid, and the activities of various antioxidant enzymes. Exogenous application of riboflavin, both as pre-sowing and foliar treatment, mitigated the harmful effects of water deficit by enhancing plant biomass, chlorophyll b, and total chlorophyll contents. Additionally, riboflavin increased total phenolic content, relative water content (RWC), and the activities of peroxidase (POD) and catalase (CAT) enzymes. Between both canola cultivars, cv. Super exhibited greater drought tolerance than cv. TM. Overall, the beneficial effects of riboflavin on canola growth under drought stress appear to be associated with improved osmoprotectant accumulation and strengthened antioxidant defense mechanisms.